Pengaruh Harga, Media Sosial Dan Kualitas Produk Terhadap Keputusan Pembelian Pada Kamang Perabot - Alfian Alfian; Jofrizal Jofrizal; Maria Magdalena; Juarsa Badri; M. Imamuddin (Journal of Innovative and Creativity, 2026)
This research aims to analyze the influence of price, social media, and product quality on purchasing decisions in Furniture Furniture in Padang City. This research uses a quantitative method with a sample of 91 respondents, which are selected using the purposive sampling technique. Data was obtained through a questionnaire and analyzed using validity tests, reliability tests, descriptive analysis, classical assumption tests, and multiple linear regressions. The results of the research are: 1) The price variable is in the good category, which shows that consumers consider the price of Kamang Furniture quite appropriate and still acceptable. 2) Social media variables are also in the good category, which means that social media has played a role in providing information and influencing consumer perception. 3) The product quality variable is in the sufficient category, so the product quality still needs to be improved, especially in terms of design, durability, and features. 4) The purchase decision variable is in the sufficient category, which shows that the level of consumer purchase decision is not optimal and needs to be improved through more effective marketing strategies